Instructor’s Role In The Conduction Of Basic Clinical Fitness In The Clinique Fitness Laboratory / Skills Laboratory - Agneta Irmarahayu Irawan; Mila Citrawati; Sri Wahyuningsih; Hikmah Muktamiroh; Tiwuk Susantiningsih (Jambi Medical Journal : Jurnal Kedokteran dan Kesehatan, 2023)
ABSTRACT Teaching clinical skills is a must in the 21st century. Medical school is required to make its graduates as skilled and professional doctors need a lot of support such as clinical skill laboratory facilities (Skills Lab) and instructors. Students need to be given sufficient opportunities to practice basic clinical skills in a place that is comfortable, safe and controlled without fear of harming patients and can be monitored and assessed in accordance with the expected competencies. Clinical skill instructors are the cornerstones of basic clinical skills teaching process. The role of the instructor includes building two-way relationships for each individual student, giving feedback, becoming role models so that students will be responsible for carrying out each procedural step of clinical skills. Their role is very important in guiding and facilitating the students to practice clinical skill, making sure their skills progress, and preparing them to obtain the predetermined competency as a doctor.